How coaching interventions impact learning organization culture, knowledge and customer experience performances: A case study comparing Thai car dealers from one US company - Sitthimet Solthong; Xavier Parisot; Vincent Ribiere (Knowledge Management & E-Learning: An International Journal)
Coaching has become an increasingly popular intervention tool for improving organizational performance. Among various benefits, coaching interventions can assist organizations with becoming learning organizations by developing a knowledge-sharing culture and strengthening knowledge flows. Nevertheless, there is insufficient empirical evidence supporting the positive impact of coaching interventions on both learning organization culture as defined in Watkins and Marsick’s model (1993) and knowledge and customer experience performances. We build upon Joo’s (2005) foundational framework for effective executive coaching by integrating the organizational learning framework. This integration aligns with the knowledge-based perspective of firms. Our enhanced research model aims to delve deeper into the effects of coaching interventions on knowledge performance and overall customer experience. The proposed model was tested on a sample of seven car dealers of a well-known US automotive company based in Thailand. Four car dealers had received coaching interventions while three had not (non-coached dealers). A total of 300 employees participated. The results demonstrate a significant positive impact of coaching interventions on all seven dimensions of learning organization culture, as well as on customer experience performance. Additionally, learning organization culture was found to partially mediate the impact of coaching interventions on customer experience performance. This study’s dual academic contributions include enriching Joo’s (2005) framework by incorporating the learning organization model and empirically examining and underscoring the positive influence of coaching interventions on learning organizations. In practical terms, coaching interventions can bolster the competitiveness of Thai car dealers through improvements in organizational performance, organizational learning, customer satisfaction, and knowledge efficiency.